Literasi Hukum Dan Kepatuhan Mahasiswa PPKn Universitas Riau Tentang Kode Etik - Ridho Kurniawan; Supentri Supentri; Radini Radini (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
However, various violations of the code of ethics are still found within the campus environment, indicating a gap between legal knowledge and student compliance behavior. This study aims to determine the effect of legal literacy on the compliance of PPKn students at the Faculty of Teacher Training and Education, Universitas Riau, regarding the Student Code of Ethics. This research employed a quantitative approach with a causal associative design. The population consisted of 333 active students, with a sample of 182 respondents determined using the Slovin formula and simple random sampling. Data were collected using a four-point Likert scale questionnaire and analyzed using simple linear regression assisted by SPSS Version 25. The results show that students’ legal literacy is in the good category with an average score of 3.08, which falls into the high category, while students demonstrate compliance with regulations with an average score of 2.93, which is also in the high category. The hypothesis testing results indicate that the t-count value of 17.694 is greater than the t-table value of 1.973, with a significance value of 0.000 < 0.05. The coefficient of determination of 63.5% shows that legal literacy significantly contributes to student compliance, while 36.5% is influenced by other factors. The higher the students' legal literacy, the higher their compliance with the campus code of ethics.